Psychosocial Interventions in Emergency Periods of Disasters - Memduha Aydın; Kürşat Altınbaş; Hazan Tomar Bozkurt; Zeynep Çalış (Genel Tıp Dergisi)
Disasters of natural origin, man-made and technological disasters are one of the current issues that always exist in our lives. Disasters are frequently heard on the world agenda and their negative effects on society are discussed. Recently, the Covid-19 epidemic has been on the agenda of the whole world as a global disaster and its effects are still ongoing. The unexpected, sudden, uncontrollable nature of disasters and their threatening to our lives are accepted as a traumatic experience with the effect of psychological destruction. In addition to meeting the basic physical needs of people who have experienced the disaster and are trying to hold on to life after the disaster, psychosocial interventions also have an important place in terms of mental health services. The purpose of this review; It is to explain the psychosocial interventions that can be applied in the emergency periods of disasters and for people who have experienced the disaster.